Evolutionary ecology of microorganisms: from the tamed to the wild - Lennon,Jay T; Denef,Vincent J (PeerJ PrePrints, 2015)
An overarching goal of biology is to understand how evolutionary and ecological processes generate and maintain biodiversity. While evolutionary biologists interested in biodiversity tend to focus on the mechanisms controlling rates of evolution and how this influences the phylogenetic relationship among species, ecologists attempt to explain the distribution and abundance of taxa based upon interactions among species and their environment. Recently, a more concerted effort has been made to integrate some of the theoretical and empirical approaches from the fields of ecology and evolutionary biology. This integration has been motivated in part by the growing evidence that evolution can happen on “rapid” or contemporary time scales, suggesting that eco-evolutionary feedbacks can alter system dynamics in ways that cannot be predicted based on ecological principles alone. As such, it may be inappropriate to ignore evolutionary processes when attempting to understand ecological phenomena in natural and managed ecosystems. In this chapter, we highlight why it is particularly important to consider eco-evolutionary feedbacks for microbial populations. We emphasize some of the major processes that are thought to influence the strength of eco-evolutionary dynamics, provide an overview of methods used to quantify the relative importance of ecology and evolution, and showcase the importance of considering evolution in a community context and how this may influence the dynamics and stability of microbial systems under novel environmental conditions.
Keywords: rapid evolution; eco-evolutionary feedbacks; traits; experimental evolution; sequencing; microbes; bacteria